2001
DOI: 10.1038/sj.onc.1204303
|View full text |Cite
|
Sign up to set email alerts
|

p14ARF homozygous deletion or MDM2 overexpression in Burkitt lymphoma lines carrying wild type p53

Abstract: The hallmark of Burkitt lymphoma (BL) is a constitutively activated c-myc gene that drives tumor cell growth. A majority of BL-derived cell lines also carry mutant p53. In addition, the p16INK4a promoter is hypermethylated in most BL biopsies and BL cell lines, leading to silencing of this gene. Activation of c-myc and/or cell cycle dysregulation can induce ARF expression and p53-dependent apoptosis. We therefore investigated the p14ARF-MDM2-p53 pathway in BL cell lines. p14ARF was expressed and localized to n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
66
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(68 citation statements)
references
References 43 publications
2
66
0
Order By: Relevance
“…8,22 Finally, another study has shown that p14 ARF , which regulates the function of p53, is frequently altered in BL cell lines carrying wt p53. 23 All these data clearly demonstrate that disruption of the p53 pathway contributes to BL development. 24,25 They also suggest that the restoration of wt p53 function in BL cells may be an efficient treatment strategy, at least in patients with cancers resistant to standard chemotherapy treatments.…”
Section: Introductionmentioning
confidence: 81%
“…8,22 Finally, another study has shown that p14 ARF , which regulates the function of p53, is frequently altered in BL cell lines carrying wt p53. 23 All these data clearly demonstrate that disruption of the p53 pathway contributes to BL development. 24,25 They also suggest that the restoration of wt p53 function in BL cells may be an efficient treatment strategy, at least in patients with cancers resistant to standard chemotherapy treatments.…”
Section: Introductionmentioning
confidence: 81%
“…Thus, these apoptotic pathways are bypassed during tumorigenesis in an independent fashion. Further, these events are relevant to the human condition, as BL have a similar frequency in hits in the ARF-Mdm2-p53 pathway (Lindstrom et al, 2001).…”
Section: Myc Triggers the Arf-p53 Tumor Suppressor Pathwaymentioning
confidence: 99%
“…It has been discovered that Bmi-1 participates in cell cycle regulation by acting as a stable transcriptional repressor of the Ink4a locus, which encodes the tumor suppressor proteins p16Ink4a and p19Arf (mouse homologue of human p14ARF). Inactivation of the p16Ink4a-pRb pathway and p14ARF-MDM2-p53 pathway by Bmi-1 deregulation has been clearly implicated in lymphomagenesis [9,10] and oncogenesis in nonsmall-cell lung cancer of human [11]. This suggested that the Bmi-1 gene plays an important role in cell proliferation and tumor progression.…”
Section: Introductionmentioning
confidence: 99%